2022
DOI: 10.31083/j.fbe1404026
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition, Physicochemical and Microbiological Characterization of Edible Seaweeds Available in the Portuguese Market

Abstract: Background:The aim of this work was the study of the proximate composition and profile of fatty acids, minerals, and some microbiological aspects of four edible seaweed species (Chondrus crispus, Palmaria palmata, Porphyra sp., and Ulva sp.) available in the Portuguese market for food consumption, and produced in a national Integrated Multi-Trophic System (IMTA). Methods: Moisture, ash, and total lipids were determined gravimetrically. Crude protein was analysed by Duma's combustion procedures. The total carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…We identifed n = 106 macroalgae items with a complete nutrient profle to estimate the PRAL [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Of these, n = 28 belonged to the Chlorophyta phylum, n = 52 belonged to the Rhodophyta phylum, and n = 26 belonged to the Phaeophyceae class.…”
Section: Sample Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identifed n = 106 macroalgae items with a complete nutrient profle to estimate the PRAL [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Of these, n = 28 belonged to the Chlorophyta phylum, n = 52 belonged to the Rhodophyta phylum, and n = 26 belonged to the Phaeophyceae class.…”
Section: Sample Descriptionmentioning
confidence: 99%
“…is based on data from References[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Ca = Calcium.…”
mentioning
confidence: 99%
“…These studies suggested that a more accurate nitrogen-to-protein conversion rate for algae is 5 (47,48), or potentially closer to 4, depending on the specific species (46). After adjusting for the conversion rate, the highest recorded protein content in red seaweed should be 30 to 35%, which is closer to the typical protein content of Porphyra spp., which ranges from 23.7 to 30% (49)(50)(51).…”
Section: Estimation Of Algal Protein Contentmentioning
confidence: 99%